(untitled) (Research, Society and Development, 2021)
Anthropogenic activities can affect the quality of mineral water, favoring the waterborne transmission of diseases. In this sense, this study aimed to evaluate the microbiological and physical-chemical quality of mineral waters sold in Belém - Pará in 20 liters, whose analyzes were carried out at LACEN-PA from 01/01/2020 to 01/ 03/2021. Fifteen samples of different brands were collected and filled in 20 liter cans and analyzed the physical-chemical and microbiological parameters, as recommended by RDC No. 275 of 22 of 2005 and RDC No. 274 of 2005. The microbiological results revealed that of the 15 samples 3 analyzed were unfit for consumption, as the presence of total Coliforms and Clostridia was detected in 1 sample and in 2 samples only total Coliforms. As for the physicochemical parameters, all samples were in accordance with the legal determination in the analyzed parameters, and the samples had a pH between 4.28 and 5.08, as stated on the label. Thus, it was observed that most of the samples analyzed were in accordance with established standards, except for three samples that showed contamination by microorganisms. However, greater rigor is needed at all stages of quality control, as well as in the distribution networks, so that the quality of the water produced is guaranteed to the final consumer.